Basic materials of construction - Erdoğan, Sinan T. (ODTÜ Yayıncılık, 2024)
Constructions that are structurally safe, serviceable and economical can only be achieved by the use of a suitable design, selection of appropriate materials, application of proper techniques, and effective inspection of the quality and performance of the materials used. Each of the above stated stages requires a sound knowledge of properties of materials.